2008
DOI: 10.1163/156856808784532581
|View full text |Cite
|
Sign up to set email alerts
|

Reflections in art

Abstract: When artists depict a mirror in a painting, it necessarily lacks the most obvious property of a mirror: as we move around the painting of the mirror, the reflections we see in it do not change. And yet representations of mirrors and other reflecting surfaces can be quite convincing in paintings. Here, we will examine the rules of reflection, the many ways that painters can break those rules without losing the impression of reflection and the rules that cannot be broken. The rules that govern the perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Using this approach, studies have uncovered various artistic strategies reflecting fundamental operations of the neural mechanisms for sensation and perception [7],[8],[12]–[14]. For example, depictions of shadows in paintings often do not correspond to the light sources that cause them [15]. Such unnoticed deviations from veracity reveal important adaptations of the brain to ecological pressures during evolution and development—in the case of shadows, the relationship of objects to light sources is in flux and therefore not a stable feature.…”
Section: First Steps In Neuroaesthetics: Sensation Perception and Artmentioning
confidence: 99%
“…Using this approach, studies have uncovered various artistic strategies reflecting fundamental operations of the neural mechanisms for sensation and perception [7],[8],[12]–[14]. For example, depictions of shadows in paintings often do not correspond to the light sources that cause them [15]. Such unnoticed deviations from veracity reveal important adaptations of the brain to ecological pressures during evolution and development—in the case of shadows, the relationship of objects to light sources is in flux and therefore not a stable feature.…”
Section: First Steps In Neuroaesthetics: Sensation Perception and Artmentioning
confidence: 99%
“…This has already brought vision scientists to look closer at paintings and link painters’ techniques with human perception ( Cavanagh, 2005 ; Di Cicco et al., 2018 ; Sayim & Cavanagh, 2011 ; van Zuijlen et al., 2020 ). For example, to depict glossiness, painters usually place a lighter spot of paint aligned with the curvature of the objects ( Cavanagh et al., 2008 ). The contrast and sharpness of this spot provide a strong cue of the perceived glossiness ( Di Cicco et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing these shortcuts can thus help us to understand how we perceive our world. These studies cover various subjects such as our perception of transparent objects ( Sayim & Cavanagh, 2011 ) or of reflections ( Cavanagh et al., 2008 ). For example, it was shown that we are not sensitive to inconsistencies in illumination in a scene ( Ostrovsky et al., 2005 ) and that many paintings exhibit such inconsistencies in favor of visual effect ( Cavanagh, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense painters have functioned as early vision scientists, discovering techniques of depiction that work for the sets of laws the visual system actually uses and revealing rules that do not. For example, observers are insensitive to impossible reflections in mirrors (eg, Croucher et al 2002 ; Bertamini et al 2003 ; Cavanagh et al 2008 ), physically inconsistent shadows (Casati 2004 ; Mamassian 2004 ; Cavanagh 2005 ) and illumination inconsistencies (Ostrovsky et al 2005 ). These unnoticed errors reveal the “naive” physics used by the visual brain to interpret scenes—a set of assumptions about the world that is in many cases quite different from real world physics.…”
Section: Introductionmentioning
confidence: 99%